1970
DOI: 10.1111/j.1471-0528.1970.tb03592.x
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Supply of the Uterus

Abstract: Summary A detailed study of the arterial system of the human uterus is described using an injection technique coupled with microradiography and histology. The micro‐vascular patterns and their variations during the menstrual cycle are illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 4 publications
4
36
0
2
Order By: Relevance
“…These findings are in line with previous studies suggesting a discontinuity exists within the myometrium itself in addition to uterine vascular organization [5,26,[34][35][36][37][38][39]. Angiographic studies described the human uterus vascularisation as an anastomotic blood supply arising from the uterine, ovarian and vaginal arteries.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are in line with previous studies suggesting a discontinuity exists within the myometrium itself in addition to uterine vascular organization [5,26,[34][35][36][37][38][39]. Angiographic studies described the human uterus vascularisation as an anastomotic blood supply arising from the uterine, ovarian and vaginal arteries.…”
Section: Discussionsupporting
confidence: 92%
“…According to histological studies [4,5], density of vasculature in the subendometrial zone is very low and this area is very thin. In a stereological study [40], Aitken et al confirmed that a decreasing gradient of vascular smooth muscle abundance (found in arteriolar and venular vessels) exists within the myometrium which is consistent with previous angiographic studies outlining the distribution of arteries and veins within the myometrium [4,5]. However, Aitken et al demonstrated also that distribution of capillaries was uniform throughout the myometrium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations